Strategi Pemasaran Pembiayaan Produk Griya Mabrur (Studi Kasus pada BSI KC Cempaka Mas Jombang) - Nasywa Kamila Nur Firdausia; Peni Haryanti; Masyudan Dardiri (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This study examines the marketing strategy for Griya Mabrur financing product in the perspective of Islamic economic at bank syariah Indonesia Kc cempaka Mas Jombang, marketing strategy activites are an interaction that seeks to create or achieve success targets which have become a sunnatullah that whatever wehave plannedm, is successful. Whether or not the provision is only in Allah SWT. The purpose of this study is to find out the methods and tactics used in marketing Griya product and whether they are in accordance with the rules of Islamic economic that have been regulated in the Al-Qur’an and Hadith. The research method used is qualitative with a descriptive approach. Data collection tecniques through interviews, observation, documentation. Data sources include Conner Bussiness Relationship Manager, Costumer Service and Customer of Bank Syariah Indonesia KC Cempaka Mas Jombang. The results of this state that the marketing strategy which is used by Bank Syariah Indonesia is very efficient and in accordance with Syakir Sula theory, namely product, price, promotion, and place. Bank Syariah Indonesia also collaborates with government agencies or institutions and distributes pamphlets through digital and direct media